2004
DOI: 10.1111/j.1600-0609.2004.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐existence of Philadelphia chromosome positive acute megakaryoblastic and B‐lymphoblastic mixed blast crisis of chronic myeloid leukemia with chronic lymphocytic leukemia

Abstract: In this study, we describe an extremely rare case of co-existence of a Philadelphia chromosome positive acute megakaryoblastic and B-lymphoblastic mixed blast crisis of chronic myeloid leukemia with chronic lymphocytic leukemia. A morphological, immunophenotypical and cytogenetic study has been performed to characterize the case and in order to identify the origin of two disorders. After the failure of the conventional therapy, the patient was treated with Imatinib with a complete hematological and cytogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Megakaryocytic blast crisis as the presenting manifestation of CML is rare. Previous studies (11,12,19), with the exception of a study by Westfall et al (20), have shown that imatinib has good effects on patients with a megakaryocytic blast crisis of CML. However, the in vitro effect of exposure to imatinib on the proliferation or apoptosis of CD34 + cells from patients with CML in the megakaryocytic crisis phase has not been described.…”
Section: Discussionmentioning
confidence: 94%
“…Megakaryocytic blast crisis as the presenting manifestation of CML is rare. Previous studies (11,12,19), with the exception of a study by Westfall et al (20), have shown that imatinib has good effects on patients with a megakaryocytic blast crisis of CML. However, the in vitro effect of exposure to imatinib on the proliferation or apoptosis of CD34 + cells from patients with CML in the megakaryocytic crisis phase has not been described.…”
Section: Discussionmentioning
confidence: 94%
“…On clinical examination, there was no hepatosplenomegaly or cutaneous lesions or symptoms related to hyperhistaminaemia. Pe-revealed the following karyotype: 46,XY [2]/46,XY,t(9; 22)(q34;q11) [4]. FISH analysis with dual colour probes for BCR and ABL genes [LSI bcr/abl Dual Colour Translocation Probe (VYSIS)] confirmed BCR/ABL fusion associated with 5 ABL deletion.…”
Section: Identification Of An Acute Basophilic Leukaemia Carrying a Rmentioning
confidence: 99%